2019
DOI: 10.1177/0379572119871715
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Nutrition in the International Food Assistance Agenda: Progress and Future Directions Identified at the 2018 Food Assistance for Nutrition Evidence Summit

Abstract: Background: Global food insecurity persists despite continued international attention, necessitating evidence-based food assistance interventions that adequately address nutritional concerns. In June 2018, the US Agency for International Development’s Office of Food for Peace through the Food Aid Quality Review (FAQR) project sponsored a “Food Assistance for Nutrition Evidence Summit” to share evidence relevant to policy and programmatic decision-making and to identify critical evidence gaps. Objective: This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(51 reference statements)
0
4
0
1
Order By: Relevance
“…Cash programs, in conjunction with traditional food assistance, may strengthen humanitarian response efforts, bring dignity and empowerment to refugees, and spill over into host communities (11). Some critics express concern that cash-based programs may not consistently demonstrate expected impacts on nutrition and other public health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cash programs, in conjunction with traditional food assistance, may strengthen humanitarian response efforts, bring dignity and empowerment to refugees, and spill over into host communities (11). Some critics express concern that cash-based programs may not consistently demonstrate expected impacts on nutrition and other public health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Development organizations first utilized cash assistance as a social protection investment to reduce vulnerability as well as increase access to resources (10). Seventy percent of food assistance provided by the World Food Program (WFP) globally went to protracted and complex emergencies with 95% of assistance delivered in direct cash in addition to food assistance (11,12). The Fill the Nutrient Gap (FNG) analysis, conducted by the World Food Program, has placed cash programs as a focus in their research on nutrition in refugee settings as an identified intervention that can decrease food insecurity and improve nutritional status of refugees (9).…”
Section: History Of Food Aid and Cash Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, en la última cumbre para la asistencia alimentaria se hizo hincapié en la necesidad de innovar en el desarrollo de alimentos que mejoren aspectos críticos en la asistencia alimentaria como la baja ingesta de proteínas y el riesgo de enfermedades crónicas producto del consumo de alimentos altos en calorías (30) . En el contexto nacional, se sugiere promover la innovación de productos alimenticios que ayuden a mejorar el perfil nutricional de las canastas.…”
Section: Discussionunclassified
“…Food assistance activities including in-kind food transfers, local/regional food assistance procurement, cash, and food vouchers have the potential to successfully address nutrition needs among vulnerable individuals [61].…”
Section: Table 1 a Comparison Between Food Aid And Food Assistancementioning
confidence: 99%